Analisis Rational Choice Theory Pada Kasus Penipuan dalam Jual Beli Online melalui Media Sosial Instagram - Vijay Gerhana Putra; Muhammad Zaky (Anomie, 2019)
This research discusses the reason why someone can become a victim in the case of online fraud through social media instagram. This research also discusses about the modes carried out by the perpetrators. Rational choice theory is used to analyze the problems in this research. This research uses qualitative method with descriptive research type. There are three informants that are interviewed in this research. Beside that, researcher also interviewed experts from National Police Headquarter and Metro Jaya Regional. The result of this research shows that the perpetrator commits fraudulent acts through instagram social media as a rational choice. They sees a big opportunity to commit fraud through Instagram, only requires a small effort but provides a very large profits. The perpetrator also see the possibility of being caught because of fraud commited through Instagram was very small.